Business strategies for electrical infrastructure engineering : capital project implementation - Wilson, Reginald, 1959- (Business Science Reference, 2013)
"This book brings together research on informed-decision making within the strategic planning sphere of system integration, highlighting social responsibility and environmental issues"--Provided by publisher